PARTISIPASI MASYARAKAT PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2014 DI KECAMATAN TAMPAN KOTA PEKANBARU - Yasmuni Anrasdi Putra; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Background of the thesis entitled "Community Participation in Legislative Election Year 2014 In Kecamatan Tampan Pekanbaru City" is knowing how much participation of the handsome district community in following the legislative elections in elections in 2014, the purpose of this study is to find out how the participation of the community of handsome district Participate in the success of the legislative election democracy party, the indicators of this research are community participation and political choice. This research uses max waber social action theory in which there is rational action. The location of this study is handsome kecamatan Pekanbaru. Furthermore, the respondents in this study amounted to 20 people, while sampling using purposive sampling technique and data collection techniques using interviews and documentation. The conclusion of this study is the level of public participation in Legislative Election Year 2014 in Kecamatan Tampan is voting, this form of political participation is very enthusiastic because almost 38%. Participation inhibiting factors are the busyness of daily activities, feelings of inadequacy and family ban and the driving factor is: firstly, the curiosity is only as a spectator of the political process now they will become the main actor. Keywords: Participation, Legislative Election, Kec. Tampan